Delivery of the Theileria parva p67 antigen to cattle using recombinant vaccinia virus: IL-2 enhances protection - Honda, Y.; Waithaka, M.M.; Taracha, E.L.N.; Duchateau, L.; Musoke, A.J.; McKeever, Declan J. (Elsevier, 1998)
To evaluate vaccinia virus as a delivery system for recombinant antigen in cattle, calves were immunized with a recombinant vaccinia virus (rVV) expressing the sporozoite surface antigen (p67) of Theileria parva (V-67) combined with those expressing bovine IL-4 (V-IL4) or IL-2 (V-IL2). The anti-p67 antibody levels detected in calves inoculated with the combination of V-67 and V-IL2. On challenge with cryopreserved sporozoites. 5 of 7 animals receiving V-67 combined with V-IL2 were protected, while those receiving V-67 in conjunction with V-IL4 behaved like unimmunized control calves. Vaccination with a recombinant virus expressing a chimaeric p67(p583)/IL2 product gave rise to a lower level of protection, whereas V-IL2 provided no immunity. The results of this study demonstrate the potential of rVV as a delivery system for use in vaccination of cattle against Theileria parva infection.